Pengaruh Brand Awareness, Brand Image, dan Brand Trust tehadap Brand Loyalty Pengguna Skincare Skintific: Studi Pada Pelanggan Moisturizer Skintific Melalui E-Commerce Shopee di Wilayah Surabaya - Indah Nurcahyani, Dina; Budi Prabowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study was conducted to determine the influence of brand awareness, brand image and brand trust on brand loyalty of skintific skincare users. This research uses a quantitative type of research with data collection techniques using questionnaire method. The population in this study is skintific moisturizer users who buy via Shopee e-commerce in the Surabaya area. This study used a sample of 100 respondents using a purposive sampling technique with the criteria with a minimum age of 17 years old, domiciled in Surabaya, and have purchased the product at least 2 time of Shopee. The data analysis technique uses multiple linear regression analysis using the validity test, reliability test, classical assumption test, F test, T test, and R2 test using the Statistical Program for Social Science (SPSS) software version 25. The results of the study show that simultaneously Brand awareness, brand image and brand trust have a positive and significant effect on brand loyalty for skintific moisturizer products. Partially, brand awareness has a positive and significant effect on brand loyalty. Brand image does not have a significant effect on brand loyalty. Brand trust has a positive and significant effect on brand loyalty.